The Rebel in the Red Jeep : Ken Hechler's Life in West Virginia Politics - Seaton, Carter Taylor (Book collections on Project MUSE., 2017)
"This biography recounts a century of accomplishments, from Hechler's introduction of innovative teaching methods at major universities, to his work as a speechwriter and researcher for President Harry Truman, and finally to his time representing West Virginia in the United States House of Representatives and as the secretary of state. In West Virginia, where he resisted mainstream political ideology, Hechler was the principal architect behind the Federal Coal Mine Health and Safety Act of 1969 and constantly battled big coal, strip mining, and fellow politicians alike. He and his signature red jeep remain a fixture in West Virginia. Since 2004, Hechler has campaigned against mountaintop removal mining. He was arrested for trespassing during a protest in 2009 at the age of 94"--Provided by publisher